The Reflections of Minimalist Approaches on the 21st Century Graphic Design - TOY, Ertan (European Journal of Multidisciplinary Studies, 2018)
Not only Graphic design, but also many other fields has changed in many ways throughout the information age. Audiences of various products have been lost within the information masses that have still been increasing day by day. Therefore, presentation and visualization of information has been becoming more important than ever. With the development of internet and mobile technologies, thousands of visual designs are being shared every day. This situation leads to visual pollution that makes communication harder with people. At this point, minimalist approaches have been played an important role to solve complexity and communication issues of design products. The main goal of minimalist approaches in design field to present an idea as the minimum numbers of colors, shapes, images and lines as possible. The purpose of this study is to investigate mentioned applications of minimal approaches in the beginning of 21st century graphic design. In order to indicate advantages and disadvantages of minimalist design methods within the context of recent graphic design samples that have been analyzed throughout this research process. As a result of these examinations, it is found that simplistic design approaches may help the people to make them understand complex information easily, which are used in graphic design products. Another finding of this research is that usability of a website, a mobile application or a product can be increased via using minimal design approaches.